2012
DOI: 10.1021/ja3084797
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Mediated Oxidative Fluorination for PET with Aqueous [18F] Fluoride

Abstract: A one-step oxidative fluorination for carbon–fluorine bond formation from well-defined nickel complexes with oxidant and aqueous fluoride is presented, which enables a straightforward and practical 18F late-stage fluorination of complex small molecules with potential for PET imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
290
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(301 citation statements)
references
References 23 publications
4
290
2
5
Order By: Relevance
“…As shown in Fig. 4, a N (37), previously prepared by transition-metal-mediated methods 12,13 , was also synthesized, in 23% incorporation yield (Supplementary Fig. 20).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 4, a N (37), previously prepared by transition-metal-mediated methods 12,13 , was also synthesized, in 23% incorporation yield (Supplementary Fig. 20).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of radiofluorine 18 F, electron-demanding ethyl benzoates were applied [24,25] and the fluorine was introduced via a nucleophilic substitution S N Ar of the trimethylammonium group in most of the cases [2]. Newer developments are developments are based on the use of iodonium salts [26,27] or nickel complexes [28] as precursors. Afterwards, the ethyl group was cleaved followed by the introduction of the succinimidyl group.…”
Section: Synthesis and Chemistrymentioning
confidence: 99%
“…Crystals 2017, 7, 90 2 of 8 developments are based on the use of iodonium salts [26,27] or nickel complexes [28] as precursors. Afterwards, the ethyl group was cleaved followed by the introduction of the succinimidyl group.…”
Section: X-ray Structure Determinationmentioning
confidence: 99%
“…The oxidative fluorination of pre-functionalized aryl metal complexes has been developed by several groups and has especially been successful for radiofluorination with [ 18 F]fluoride. In 2012, the Ritter group reported that arylnickel(II) complexes could be used for the regioselective synthesis of aryl fluorides, with a combination of a fluoride source such at TBAT and hypervalent iodine oxidant 13 [179]. The nickel-mediated oxidative fluorination reaction enabled a one-step radiofluorination of arylnickel(II) complexes (synthesized by oxidative addition of an aryl halide to a Ni(0) precursor) using aqueous [ 18 F] fluoride and oxidant 13 (Fig.…”
Section: Oxidative Arene Fluorination With Fluoridementioning
confidence: 99%